An expert panel delphi consensus statement on patient selection and management for transitioning between oral and inhaled treprostinil. (February 2021) - Rahaghi, Franck F.; Allen, Roblee P.; Balasubramanian, Vijay P.; Chakinala, Murali M.; Elwing, Jean M.; Feldman, Jeremy; Leary, Peter J.; Rischard, Franz; Safdar, Zeenat; Sood, Namita; Oudiz, Ronald J.
Abstract: Treprostinil, a prostacyclin analogue used in the treatment of pulmonary arterial hypertension (PAH), is available for administration by parenteral, oral, or inhaled routes. Transitioning between routes may be beneficial for appropriate patients; however, there is little published data on transitions between oral and inhaled treprostinil. We used a modified Delphi process to develop expert consensus recommendations on transitions between these formulations. Three questionnaires were used to develop statements about relevant aspects of transition management, which the panelists rated, using a Likert scale, from −5 (strongly disagree) to +5 (strongly agree). Eleven physicians with expertise in PAH treatment modalities, participated in the panel. Of the 492 statements evaluated, consensus was reached on 215 (43.7%). Key consensus recommendations included (1) accurately defining successful transition, as stable or improved PAH with good tolerability and adherence, and (2) patients with stable, low-risk PAH showing insufficient response or tolerability to their existing treprostinil therapy (and due to restrictions in up titration of dosing), as appropriate candidates for transitions between treprostinil formulations. Panelists did not reach consensus for an overall strategy for performing these transitions, mainly because of variability in their practice parameters. Consensus was also achieved on recommendations for adverse event management, including reassurance, administration of oral treprostinil 3 times daily with food, and dosing inhaled treprostinil at intervals ≥3 hours apart. The Delphi process aided in developing expert consensus recommendations that may provide clinically useful guidance for transitioning between treprostinil formulations. However, additional data from centers with high volumes of PAH patients undergoing treprostinil transitions would be optimal for defining more complete and robust strategies to facilitate successful transition.